Environmental Education in Rural Quilombos in the Southern Region of Rio Grande do Sul - Ottoni Marques Moura de Leon; Karine Ferreira Sanchez; Maiara Moraes Costa; Diuliana Leandro; Larissa Medianeira Bolzan; Fábio Andre Mayer (Universidade Federal do Norte do Tocantins, 2023)
The present study aims to ascertain whether the "Morando Bem no Quilombo" project, funded by Caixa Federal and implemented by the Center for Support and Promotion of Agroecology (CAPA) in 2018 and 2019, aligns with the precepts of environmental education and fosters sustainable solutions. The objective of this research was to identify the presence of environmental education within the "Morando Bem no Quilombo" project. To achieve this goal, the methodology involved conducting meetings and organizing conversation circles with the community, providing insights into the execution process of the Morando Bem no Quilombo project. The research results indicate that the project sparked discussions regarding its alignment with the field of environmental education. It can be concluded that the project embraced the principles of liberating environmental education by aiming to generate knowledge, sustainability, autonomy, and empowerment.